Eavesdrop at Clinical Depths: Deep Photoacoustic Imaging with Internal Light Illumination - Joseph J. Yang; Soon-Woo Cho; Junjie Yao (Advanced Devices & Instrumentation)
Photoacoustic imaging (PAI) is a hybrid image modality that combines optical absorption contrast and acoustic detection of light-induced ultrasound waves. PAI can produce high-resolution and molecular-sensitive images of deep tissues, which are useful for various preclinical studies, such as brain functions, cancer therapy, and vascular imaging. However, PAI faces the challenge of strong optical attenuation in biological tissues, which limits the imaging depth of conventional PAI to several centimeters. Many clinically relevant organs are located near body cavities, which offers the opportunity to navigate a catheter-based device for internal-illumination PAI. By delivering light directly to the target through an optical fiber, internal-illumination PAI can effectively overcome the optical attenuation problem and achieve imaging depths of more than 10 cm while maintaining the resolution, signal-to-noise ratio, and functional and molecular sensitivity of PAI. Thus, internal-illumination PAI has great potential for medical applications. This review introduces the principles and applications of different internal-illumination PAI modalities: photoacoustic endoscopy, internal-illumination photoacoustic tomography, and photoacoustic-guided ablation. We highlight the current research directions and challenges and discuss the future opportunities.